Amigurumi loveys & blankets : 16 adorable animal projects to crochet & snuggle - Wimsett, Ariana (Landauer publishing, 2024)
"Features 16 amigurumi projects, animals in both a lovey and a blanket version, along with crochet basics, stitches, and finishing techniques"--